Noise Attenuation of a Duct-resonator System Using Coupled Helmholtz Resonator - Thin Flexible Structures - Iwan Prasetiyo; Gradi Desendra; Khoerul Anwar; Mohammad Kemal Agusta (Journal of Engineering and Technological Sciences, 2021)
Several studies have been devoted to increasing the attenuation performance of the Helmholtz resonator (HR). One way is by periodic coupling of HRs in a ducting system. In this study, we propose a different approach, where a membrane (or a thin flexible structure in general) is added to the air cavity of a periodic HR array in order to further enhance the attenuation by utilizing the resonance effect of the membrane. It is expected that three attenuation mechanisms will exist in the system that can enhance the overall attenuation, i.e. the resonance mechanism of the HR, the Bragg reflection of the periodic system, and the resonance mechanism of the membrane or thin flexible structure. This study found that the proposed system yields two adjacent attenuation peaks, related to the HR and the membrane respectively. Moreover, extension of the attenuation bandwidth was also observed as a result of the periodic arrangement of HRs. With the same HR parameters, the peak attenuation by the membrane is tunable by changing its material properties. However, such a system does not always produce a wider attenuation bandwidth; the resonance bandwidths of both mechanisms must overlap.